Deteksi Cepat Formalin Menggunakan Zat Warna Kelopak Bunga Rosella ((Hibiscus Sabdariffa L.) Pada Berbagai Produk Pangan Basah - Desi Tirtawati; Mardiah; Siti Irma Rahmawati (Universitas Djuanda, 2025)
One of the dangerous substances still used in food goods as a preservative is formalin. The public finds it challenging to identify food products that contain formalin because formalin testing has so far been done in labs using chemical reagents. Formalin may be identified using anthocyanin dyes, according to the findings of multiple studies. Anthocyanin dyes are reported to be present in rosella flowers. Finding out if rosella flower extract can be utilized to detect formalin in different wet food products was the aim of this investigation. Using water and ethanol solvents, fresh rosella flower petal extract and dried rosella were prepared in different ratios of 1: 4, 1: 6, and 1: 8. The resulting food product samples were then tested on white tofu, lontong, and yellow noodles. The color changes that transpired in samples that were provided liquid rosella flower petal extract and the paper kit test were used to conduct qualitative observations. Formalin identification was analyzed by comparing the qualitative and quantitative findings of laboratory tests. The study's findings demonstrated that food samples containing formalin with a pH of greater than 8 underwent a color shift. In the paper kit test of fresh Rosella flower petal extract, the red color turned yellow and went from red to greenish blue. While the results of observations of color changes using dried rosella flower petal extract were more difficult to detect because the color was too thick. The fresh rosella flower petals ethanol extract with a 1:8 ratio produced the best results.